Primordial patterns. - Koh, Cheng Guan. (2011)
This thesis is an exploration of various ancient cultures from around the world, namingly the Ancient Egypt, Maya, Aztec and Babylon. As we put the elements and characteristics of each culture together, patterns start to emerge, the study of Jung's theory of the archetypes are introduced to help explain the repeating patterns across the cultures.The research started as a general study of the famous Egyptian ancient architectures, the pyramids, all studies and researches surrounding it, be it facts, speculations based on observations, speculations based on pure facts, and so on. This endless chase for more studies and researches for the pyramid has lead me to also look into other ancient architectures such as the Mayan's El Mirado La Danta, Templo Mayo and other magnificent constructions. As I go deeper into the research, I start to notice many overlapping themes and patterns from different cultures around the world.